ISLAM, POLITICS AND IDENTITY IN WEST SUMATRA (State Islamic University (UIN) of Sunan Ampel Surabaya, 2013)
Since Indonesia has undergone a decentralisation phase, its regions have searched for their local identities. In West Sumatra, for instance, Islam is dominant. Consequently, there has been a constant attempt to infuse Islamic values into social, political and economic aspects. The paper seeks to contextualise the key phases in the history of West Sumatra in the broader history of the archipelago and the Malay world, and to show how key events in West Sumatra and at the national level set the parameters for later debates about Islam and identity in the region. The paper argues that now, as in the past, the relationship between Islam, a global religion, and Minangkabau culture was, and is, simultaneously contested. It is also found that Islam as an ideology was subordinated after Independence days, and again under the New Order. The strong association between Islam and regional identity only solidified in the post-Suharto. Now, regional governments has been utilising claims that local customs are based on Islam and Islam is based on the Qur’an.